STRENGTHENING OF THE LEGAL BASIS OF CIVIL SOCIETY INSTITUTIONS IN THE NEW TAHRI CONSTITUTION OF UZBEKISTAN (TAMADDUN NURI JURNALI, 2024)
This article talks about the changes introduced in the newly revised Constitution of Uzbekistan regarding the institutions of civil society and the further strengthening of the legal basis of these institutions as a result of them.